Process analysis and improvement : Tools and techniques - Seppanen, Marvin S. (The Mcgraw-Hill/Irwin Series in Operations and Decision Sciences, 2005)
Contents of the book include: Introduction to Process Analysis and Improvement, Process Analysis and Improvement Using Visio, Applications Using Visio,....